PENGARUH SOSIALISASI PERATURAN LALU LINTAS TERHADAP SIKAP SISWA SMA DI BANGKINANG KOTA - Asrul Sani; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Traffic Police Unit resorts Kampar is an agency of the Traffic Police organizations which are directly under the Chief of Police located in the center of the city Bangkinang responsible for Kampar Riau either a traffic violation or accident lintas. Based on data from Laka Police Kampar the number of accidents in Bangkinang City in 2015 amounted to 24 accidents in which learners more of these casualties are 12 casualties, and for a traffic violation in terms of profession, high school students is quite alarming from one month to a year 2015 is a 712 violations in which the position of the highest student ranks first in the list of violations. With the above problems Traffic Police Kampar conduct socialization activities traffic regulations with the intent and purpose of that public road users especially students know, understand and believe the traffic police as protectors and servants of the people in the activities of Community Education of traffic, traffic enforcement, assessment of traffic problems, registration and identification of motor vehicle and the driver, for the achievement of security, order and smooth traffic. The method used in this research is quantitative method. Collecting data using questionnaires, and documentation. To determine the influence of the socialization of traffic regulations on the attitudes of high school students, the authors use simple linear regression analysis. Variabel X in this study is an activity socializing traffic regulations, while variable Y is the attitude of high school students in City Bangkinang. Number of samples in this study were 92 students by using the sampling technique is Taro Yamane. data processing program tested using Statistical Product And Service Solution (SPSS) Windows version 20. The results showed the influence of the socialization of traffic regulations on the attitudes of high school students in City Bangkinang. This is based on data analysis using simple linear regression is Y = 6.009 +, 565 X. Numbers constant (a) of 6.009 and a coefficient of socialization variables, t 7.790 565 with greater when compared with t table 1, 987 and a significance level , 000 is smaller than α = 0.05. Therefore H1 accepted and H0 is rejected because there is significant influence between socialization activities regulation